Pollutants of Wastewater Characteristics in Textile Industries - S.M. Imtiazuddin,; Majid Mumtaz ,; Khalil A. Mallick, (Journal of Basic & Applied Sciences, 2012)
Textile Industry is one of the most important and largest industrial sectors in Pakistan. It has a high importance in terms of its environment impact, since it consumes large quantity of textile industrial processed water and produces highly polluted discharge water. The textile industry uses high volume of water throughout its operation, from the washing of fibers to bleaching, mercerizing, dyeing, printing and washing of finished products. A process data collection was performed and integrated with a characterization of the process effluents in terms of treatability and reusability. In order to evaluate properly the wastewater loading, on analysis course was set. The samples were collected during four months period of time i.e. November, December, January and February 2009-2010 from the seven samples were collected from different textile mills and analyzed for various parameters such as Total Dissolved Solids(TDS), Chemical Oxygen Demand(COD), Biochemical Oxygen demand(BOD), pH, Electrical Conductivity(EC), and heavy metals like Cadmium(Cd), Chromium(Cr), Copper(Cu), Iron(Fe), Manganese(Mn), Nickel(Ni), Potassium(K), Phosphorous(P), Sodium(Na), Sulphur(S), Zinc(Zn) were found in within the limits. Concentrations of all these metal ions in the effluent were above the recommended NEQS. It was therefore concluded that textile effluents were highly polluted.